Modern Approaches to Development of Schoolchildren Up-Bringing: Searching Theoretical and Methodical Invariants - L I Klochkova (Peoples' Friendship University of Russia (RUDN University), 2013)
This article discloses the modern approaches to schoolchildren up-bringing which enrich the practical work at school proceeding from the variety of educational systems, different up-bringing programmes in the school activity, organizing social projects, providing the conditions for the creative activity of children and adults and so on.